The Mediating Effect of Social Emotional Learning between Relationship on Basic Psychological Needs and Technology Addiction - Murat Agirkan (Journal of Education in Science, Environment and Health)
This study was aimed at testing the hypothetical model, which included technology addiction, basic psychological needs, and social emotional learning skills (SEL). The study also examined whether there is a mediating effect of SEL in the relationship between basic psychological needs and technology addiction. For this purpose, data were collected from a sample of 592 participants [424 (71.6%) females and 168 (28.1%) males] aged between 18 and 27 years. Demographic Information Form, Basic Psychological Needs Satisfaction and Inhibition Scale, Social Emotional Learning Scale-Young Adult Form (SELS-YF), and Technology Addiction Scale (TAS) were used to collect the data. Equation Modeling (SEM) was used to analyze the data, and the results supported the hypothetical model. There was a negative correlation between technology addiction and the satisfaction of basic psychological needs and SEL. There was a positive correlation between the satisfaction of basic psychological needs and SEL. Another finding was that SEL indirectly effected the relationship between satisfaction of basic psychological needs and technology addiction. In addition, the model explained about 14% of the total variance in technology addiction.